Isolation and Morphological Characterization of Lead Tolerant Bacteria Associated with Perna viridis - Yoshua Mario Sumbodo; Fiona Aqhila Dewi; Okti Hajeng Kristiadi; Annisa Nur Ayuningtyas; Heksa Raihan; Muhammad Zainuri; Hermin Pancasakti Kusumaningrum (Buletin Oseanografi Marina, 2023)
Lead is a heavy metal contamination that is released into sea waters and cannot be decomposed so it accumulation and magnification along the food chain. Efforts to explore bacteria that have tolerance and have the potential to become lead reduction agents are a strategic step in remediating lead contamination. One mechanism for lead bioremediation by bioaccumulation is to utilize metallothionein protein which can potentially be obtained from isolates of green mussel associated bacteria. Bacterial isolates associated with green mussels were obtained by isolating the bacteria and testing the tolerance of the bacterial isolates using Luria Bertani media which was added with Pb(NO3)2 at a concentration of 100 ppm and its multiples to determine their tolerance to lead. The bacterial isolates obtained were characterized based on colony and cell morphology. The results of the lead resistance test carried out showed that 11 bacterial isolates were obtained and 3 bacterial isolates had tolerance to lead with a lead concentration of 400 ppm. Bacterial isolates that are tolerant to lead show changes in cell morphology to reduce the impact of exposure to lead which has a lethal effect, because the resulting decrease in cell surface area can reduce lead absorption.